The Effect of Tourism Event Management on Tourist Loyalty with Visitor Satisfaction as Mediating Variable - Sukardi Silalahi (Jurnal Ilmiah Manajemen Kesatuan, 2026)
Increasing tourism competition requires effective event management strategies. This study aims to analyze the influence of tourism event management on tourist loyalty through the mediation of visitor satisfaction. A quantitative approach was employed, surveying 200 tourists who visited Lake Toba between November and December 2025. Data were collected using a structured five-point Likert scale questionnaire and analyzed through SEM-PLS. The results of the study indicate that tourism event management has a positive and significant effect on visitor satisfaction. Furthermore, visitor satisfaction is proven to have a positive and significant effect on tourist loyalty. In addition, visitor satisfaction acts as a significant mediating variable in the relationship between tourism event management and tourist loyalty. These findings indicate that the quality of professional event planning, organization, implementation, promotion, and evaluation can create memorable tourism experiences, increase satisfaction, and build sustainable tourist loyalty. In addition to practical implications for local governments, destination managers, and event organizers in creating integrated, creative, and experience-oriented tourism event management strategies to boost Lake Toba’s competitiveness as a top national and international tourism destination, this study makes theoretical contributions to the development of event management studies and tourist behavior.